Judges' Legal Culture in Dealing with High Number of Applications for Child Marriage Dispensation during Covid-19 Pandemic at the Kudus Religious Court - Supriyadi; Siti Suriyati (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
This study aims to explore the judges' legal culture in the Kudus Religious Courts in dealing with the high number of applications for marriage dispensation during the Covid-19 pandemic. Making a decision on a case becomes problematic for judges because they have to make it on their personal considerations. This research was analyzed qualitatively using a constructivism paradigm with a socio-legal research approach based on primary data by interviewing 2 (two) judges, 3 (three) advocates, and 3 (three) applicants for a marriage dispensation. Moreover, it also employed secondary data, including the marriage law, marriage regulation and its implementation, relevant literature, and academic journals. The research findings are: First, the high number was caused by Kudus people’s perception of the minimum legal age of marriage which is based on customary belief, which is maturity in social life, rather than legal regulation which is numerical age. Second, in making a decision about the case, the judges make considerations based on legal facts in the trial court and the values of justice living in the society while paying attention to the Supreme Court rules. Third, the legal culture of judges in deciding the application is making dialogue with some fellow judges while advising applicants to revoke their application.